Hearing Evaluation of Neonates with Hyperbilirubinemia by Otoacoustic Emissions and Brain Stem Evoked Response Audiometry - Mirajkar, Swapnil Chandrakant; Rajadhyaksha, Surekha (Journal of Nepal Paediatric Society, 2017)
Introduction: Neonatal hyperbilirubinemia is one of the most important factors affecting the auditory system and can cause sensorineural hearing loss. This study evaluated the hearing status in neonates with hyperbilirubinemia and results obtained from Otoacoustic emissions (OAE) and Brain stem evoked response audiometry (BERA) analysis were compared with each other’s. Material and Methods:This study was performed on fifty eligible term neonates with hyperbilirubinemia requiring either phototherapy or exchange transfusion or both. Hearing analysis was done by OAE and BERA. Results: Out of fifty eligible neonates, twenty one (42%) had hearing impairment as per OAE analysis, eight (16%) had hearing impairment; two (4%) neonate had inconclusive hearing analysis as per BERA analysis. Out of twenty one neonates having hearing impairment by OAE only five had hearing impairment as per BERA analysis. While the eight neonates who had hearing impairment by BERA analysis, five had hearing impairment by OAE. Conclusion: The study showed hearing impairment by OAE analysis in 42% neonates while the BERA analysis showed hearing impairment in 16 % neonates. The increased level of Serum bilirubin has not shown the increase in percentage of hearing impairment. J Nepal Paediatr Soc 2016;36(3):310-313